New Diquinazoline Derivatives: Synthesis and Evaluation of Anti-Bacterial Activity - Ameer A. Hussein (Journal of Global Pharma Technology, 2016)
Oxazine and quinazoline has a very important in organic chemistry especially in hetero cyclic fields. this research consist the preparation of 4H,4'H-2,2'-bibenzo[d][1,3]oxazine-4,4'-dione compound (1) from di acid chloride with 2-aminobenzoic acid in pyridine as solvent to give compound (2) 3,3'-diamino-2,2'-biquinazoline-4,4'(3H,3'H)-dione .compound 2 include free amino group .this compound was reacted with maleic and phthalic anhydride for synthesized of cyclic imide compounds (3,4).another reaction for compound 2 with some substituted aromatic aldehyde for prepared of some novel Schiff bases (5-9) contains quinazoline ring. compound 1 was treated with sulfathiazole and sulfadiazine for synthesized of sulfa compounds contains sulfone amide groups (10,11).compounds (12,14) were prepared from the reaction of 4H,4'H-2,2'-bibenzo[d][1,3]oxazine-4,4'-dione with some primary amine p-aminoacetophenone ,p-amino acetanilide to product of (12,13) but compound 14 was prepared from reaction of of compound 1 with 3-amino-2-phenylquinazolin-4(3H)-one to give compound 14 consist four rings of quinazoline. all synthesized compounds were measured for antibacterial activity and the structures of quinaolines were confirmed by thin layer chromatography, melting points ,Fourier transform infrared, H-NMR, elemental analyzer.Keywords: Dioxazine, Diquinazoline, dicyclicimide,antibaterials.